231 Radiographic Assessment of Inflatable Penile Prosthesis Reservoir Location Variability in Contemporary Practice. Issue 1 (1st April 2022) - Kavoussi, M; Cook, G; Nordeck, S; Dropkin, B; Joice, G; Sanders, S; Pruitt, J; Hudak, S; Morey, A
ABSTRACT: Introduction: Inflatable penile prosthesis (IPP) reservoirs are typically placed into the Space of Retzius (SOR), High Submuscular Space (HSM), or alternative locations via a transinguinal (TI) approach or a lower abdominal counter incision (CI). A cadaver study showed variability in reservoir location after TI-HSM placement (JSM: 2016 Sep;13(9):1425-1431). Objective: We sought to evaluate reservoir location using cross-sectional imaging following contemporary IPP insertion. Methods: We retrospectively reviewed our institutional database and identified men who underwent virgin penoscrotal IPP insertion from 2007 to 2019. We then identified those men who subsequently underwent cross-sectional imaging prior to October 2019. Radiologists blinded to reservoir placement technique evaluated cross-sectional imaging and categorized each reservoir location in relation to the abdominal wall musculature, transversalis fascia, and peritoneum. Statistical analysis was performed using Chi-squared and Fisher's exact tests. Results: Among 561 men who underwent virgin IPP insertion during the 12 year study period, 114 had cross-sectional imaging subsequently obtained: 29 TI-SOR, 80 TI-HSM, and 5 CI-HSM (Table). TI-HSM reservoirs were more likely than TI-SOR to be located anterior to the transversalis fascia (14 vs. 48%, p=0.001). TI-HSM reservoirs were less likely than TI-SOR to be located in the preperitoneal space (62 vs. 18%, p<0.001). Rates of retroperitoneal reservoir location were similar between the TI-HSM and TI-SOR groups. Among all 561 patients (131 TI-SOR, 405 TI-HSM, and 25 CI-HSM), rates of reservoir-related complications requiring operative intervention were similar between groups (5 vs. 2 vs. 0%, p = 0.24). Conclusions: Roughly half of the TI-HSM reservoirs in this series appeared to be located posterior to the transversalis fascia on cross-sectional imaging. Although preperitoneal and retroperitoneal locations were common in both groups, reservoir related complications were rare. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Boston Scientific and Coloplast